Exploring Dimensions of Teacher Education in Nepal: Perspectives, Challenges, and Reform Opportunities - Yadu Prasad Gyawali (MASI Mandiri Edukasi, 2023)
This study evaluates Nepal's English Language Teacher Education (ELTE) reform possibilities and challenges. The study examines teacher education in connection with social contexts, knowledge transformation, and knowledge generation from many perspectives. Reflective teaching, modelling, and research habits improve instructors' professionalism and create effective learning environments. According to the report, English Language Teachers in Nepal face obstacles that must be addressed in teacher education. Content analysis is used to study the diverse literature. Surkhet English teachers and headteachers participate in a focus group. The paper's results and discussion section summarize the literature review and participants' opinions. It covers key concerns such as the absence of physical facilities and funds for teacher training, poor English language ability among instructors, coordination issues between pre-service and in-service training programs, and minimal research on ELT classroom methods. Reforming teacher education to improve topic knowledge, pedagogical skills, and technology expertise is recommended. English language teacher education faces societal inequities, uneven government regulations, and limited access to internet resources and databases. The study also examines technology integration in English language classrooms, online platforms, and the lack of research on ICT integration in Nepalese education. This research article helps to understand ELTE in Nepal and suggests areas for development and additional study.